Pancreatic Ductal Adenocarcinoma With High Radiotracer Uptake in 68Ga–Prostate-Specific Membrane Antigen PET/CT. (September 2017) - Sahbai, Samine; Rieping, Petra; Pfannenberg, Christina; la Fougére, Christian; Reimold, Matthias
Abstract : Abstract: Prostate-specific membrane antigen imaging with PET/CT is increasingly used in prostate cancer and was shown to have a high diagnostic performance. We report a clinical case of a 67-year-old man with previous history of operated prostate cancer and increasing prostate-specific antigen blood level. 68 Ga-HBED-CC prostate-specific membrane antigen PET/CT imaging was indicated for the assessment of local recurrence and lymph node metastases of prostate cancer. In addition, a soft tissue mass in the body of the pancreas with high radiotracer uptake was detected. Histopathology confirmed a pancreatic ductal adenocarcinoma.